The use of elie wiesel's testimonial literature in the book “night” in elementary school English classes: a methodological proposal - SANTOS, Daise da Conceição Matos (2023)
The present study carried out within the scope of the Full Degree in English Literature by the Faculty of Foreign Languages of the Federal University of Pará, Bragança campus, aims to propose a methodological proposal for English classes in basic education using the work Night, which is included within the testimonial literature field. The proposal intends to put students in contact with literature in the classroom in English classes, where it aims to achieve an increase in the teaching-learning process of the students, in a way that works on reading, writing, creativity, collective work and reflections on other cultures and historical facts. In a theoretical way, based on studies by Luciana Severino da Silva, Daniela Tiberio, Seligmann-Silva, Wilberth Salgueiro, among other intellectuals, we seek to understand how literature is important for students in English language classes in basic education, but that for some reasons teachers usually stop working in this area. As a methodological perspective, this research is of an analytical-bibliographical nature, where we sought to understand literature and education, using testimonial literature in the classroom as a possible way to teach the subject of English in elementary school.